All-union school of metrical number theory in Palanga - Journal, Lithuanian Mathematical (Lithuanian Mathematical Journal, 1966)
Original title in Russian and Lithuanian:Всесоюзная школа по метрической теории чисел в ПалангеVisasąjunginė metrinės skaičių teorijos mokykla Palangoje